UPAYA MENINGKATKAN ANIMO CALON MAHASISWA MENGGUNAKAN STRATEGI BAURAN PEMASARAN: Marketing Jasa Pendidikan - Prayitno, Dedi (PRIMA EKONOMIKA, 2025)
The number of new students that tends to decrease is the reality of the condition and positioning of the Physiotherapy Academy in the minds of consumers/students that needs to be monitored and evaluated to strive to become a solution in society. This research is intended to describe the marketing mix of educational services at the Yogyakarta "YAB" Physiotherapy Academy by focusing on products, prices, location, promotions, human resources, physical evidence, and the lecture process. This research was conducted using a qualitative descriptive method. The data was obtained by direct interviews with resource persons, heads of marketing teams, databases, structural officials in the field of infrastructure and several students as users, environmental observations that support research and documentation studies. This research uses a flow analysis model. Community expectations and reality regarding the "YAB" Physiotherapy Academy still need to be optimized, especially regarding cost transparency, facilities/campuses and human resource management that need to be improved so that productivity increases. It is necessary to further optimize the monitoring and evaluation of the marketing mix for the "YAB" Academy of Physiotherapy educational services regarding activities regarding product promotion, price, location, physical evidence/infrastructure, as well as the process of activities of the entire academic community.